Exploring path dependence, policy interactions, and actor behavior in the German biodiesel supply chain. (1st June 2017) - Moncada, J.A.; Junginger, M.; Lukszo, Z.; Faaij, A.; Weijnen, M.
Highlights: The effects of both agricultural and bioenergy policy interventions are explored. The timing of intervention of bioenergy policies determined the system's evolution. A lack of agents' adaptation mechanism led to a decrease in biodiesel production. System behavior is influenced by individual behavior which is shaped by institutions. Abstract: Biofuel production is not cost competitive and thus requires governmental intervention. The effect of the institutional framework on the development of the biofuel sector is not yet well understood. This paper aims to analyze how biofuel production and production capacity could have evolved in Germany in the period 1992–2014. The effects of an agricultural policy intervention (liberalization of the agricultural market) and a bioenergy policy intervention (a tax on biodiesel after an initial exemption) are explored. Elements of the Modeling Agent systems based on Institutional Analysis (MAIA) framework, complex adaptive systems (CAS) theory, and Neo Institutional Economics (NIE) theory were used to conceptualize and formalize the system in an agent-based model. It was found that an early liberalization of the agricultural market led to an under-production of biodiesel; a late liberalization led to the collapse of biodiesel production. An early introduction of the biodiesel tax led to stagnation in biodiesel production and production capacity; a late introduction led to an increase in sunk costs provided that the biofuel quota is binding. Also, a lack of agents' adaptation mechanism to forecast prices led to a decrease in patterns of biodiesel production when an external shock was introduced in the system. In sum, we argue that system behavior is influenced by individual behavior which is shaped by institutions.